Different Withering Times Affect Sensory Qualities, Chemical Components, and Nutritional Characteristics of Black Tea - Bernard Ntezimana (MDPI AG, 2021)
The present study emphasizes the effect of withering time set at 4 ± 0.5 h (WT4), 6 ± 0.5 h (WT6), 8 ± 0.5 h (WT8), 10 ± 0.5 h (WT10), and 12 ± 0.5 h (WT12) on the sensory qualities, chemical components, and nutritional characteristics of black tea. The sensory evaluation revealed high total quality scores at WT8 and WT10. Polysaccharides, amino acids, and soluble sugars significantly increased with an increase in withering time, and an apparent peak value was obtained at WT10. However, polyphenols, flavonoids, glycosides, organic acids, catechins, alkanoids, and theaflavins decreased with an increase in withering time. With an increase in withering time, the content of aromatic substances showed a trend of increasing first and then decreasing. The peaks of alcohols, aldehydes, and acids appeared at 10 ± 0.5 h, 10 ± 0.5 h, and 8 ± 0.5 h, respectively. The content of esters, ketones, and hydrocarbons showed a downward trend with an increase in withering time. Aroma analysis revealed that withering time could not exceed 10 ± 0.5 h. Black tea withered up to WT10 showed enhanced inhibition of α-glucosidase and α-amylase activity with good sensorial attributes. Glucose uptake inhibition capacity increased up 6 ± 0.5 h and then decreased, while antioxidant capacity decreased with an increase in withering time. The overall results show that the 8 ± 0.5 h to 10 ± 0.5 h withering time could improve black tea quality and nutritional characteristics.